EFEKTIFITAS PEMBERDAYAAN USAHA PROGRAM GERBANGMAS-TASKIN UNTUK PENGENTASAN KEMISKINAN PADA UNIT PELAKSANA KEUANGAN (UPK) DI KOTA BANJARBARU - Muhammad Muthahhari Ramadhani (Gapenas Publisher, 2021)
The South Kalimantan Community Development Integrated Movement for Poverty Alleviation has been implemented by the Human and Environmental Empowerment Activity unit carried out by the Implementing Team (Timlak) in the form of grant assistance. The results can be directly felt by the target households of the program. However, in the implementation of business empowerment, it is known that every Financial Implementing Unit (UPK) in Banjarbaru City faces almost the same problem, namely the inability to repay loans (arrears) every month by program recipient households. This research was conducted using a descriptive evaluative research approach. In practice, this research is intended to evaluate the effectiveness of business empowerment of the Gatemas Taskin Program in Banjarbaru City in business development and increasing the income of poor households as potential program targets. The results showed that the implementation of the Integrated Community Development Movement Program (Gerbangmas-Taskin) for Poverty Alleviation in Banjarbaru City, was considered ineffective in helping business development and increasing the income of poor households. This is because the program recipients are not households that meet the target household criteria (RTS), namely poor households (RTM) who receive direct cash subsidies so that the program targets to help the poor develop businesses and increase their income cannot be achieved or are not on target. This fact shows that the Gerbangmas Taskin Program has not implemented microfinance principles, one of which is that aid is only for the poor. Factors causing the program's ineffectiveness are non-poor household beneficiaries (contrary to microfinance principles), lack of understanding of UPK programs, low participation, and suboptimal assistance